REIMAGINING THE CANON: ANALYZING ADAPTATIONS OF SHAKESPEARE’S PLAYS AND JANE AUSTEN’S NOVELS IN CONTEMPORARY FILM AND MEDIA - Gupta, Roopa (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The adaptation of literary classics into film and television serves as a dynamic bridge connecting traditional literature with contemporary media, offering new avenues for audiences to engage with time-honored narratives. This paper examines the adaptation process through the lens of William Shakespeare’s plays and Jane Austen’s novels, focusing on the intricate balance between fidelity to the original texts and the creative liberties taken by filmmakers. Drawing on adaptation theories by Linda Hutcheon and Robert Stam, the study explores how adaptations serve not merely as reproductions but as re-interpretations that reflect evolving social, cultural, and artistic contexts. Through detailed case studies—including Baz Luhrmann’s Romeo + Juliet (1996), Akira Kurosawa’s Throne of Blood (1957), Ang Lee’s Sense and Sensibility (1995), and Amy Heckerling’s Clueless (1995)—this paper investigates how filmmakers preserve the thematic core of the original works while employing cinematic techniques to enhance or transform their meanings. The analysis delves into aspects such as cultural transposition, modernization, and audience reception, demonstrating that adaptations often engage in a dialogic relationship with their source material. Key themes such as the tension between tradition and innovation, the role of cultural context, and the impact of modern interpretations are discussed to illustrate how adaptations not only keep classic literature alive but also enrich it with contemporary relevance. This continual reimagining ensures that canonical works remain vibrant, accessible, and meaningful in an ever-evolving cultural landscape. Ultimately, the study underscores the significance of adaptations in preserving and transforming literary heritage, fostering a deeper and more dynamic engagement with classic texts across generations.